Insights into sensitivity analysis of Earth and environmental systems models: On the impact of parameter perturbation scale. (September 2017) - Haghnegahdar, Amin; Razavi, Saman
Abstract: This paper investigates the commonly overlooked "sensitivity" of sensitivity analysis (SA) to what we refer to as parameter "perturbation scale", which can be defined as a prescribed size of the sensitivity-related neighbourhood around any point in the parameter space (analogous to step size Δ x for numerical estimation of derivatives). We discuss that perturbation scale is inherent to any (local and global) SA approach, and explain how derivative-based SA approaches (e.g., method of Morris) focus on small-scale perturbations, while variance-based approaches (e.g., method of Sobol) focus on large-scale perturbations. We employ a novel variogram-based approach, called Variogram Analysis of Response Surfaces (VARS), which bridges derivative- and variance-based approaches. Our analyses with different real-world environmental models demonstrate significant implications of subjectivity in the perturbation-scale choice and the need for strategies to address these implications. It is further shown how VARS can uniquely characterize the perturbation-scale dependency and generate sensitivity measures that encompass all sensitivity-related information across the full spectrum of perturbation scales. Highlights: Model sensitivity analysis is "sensitive" to parameter perturbation scale (e.g., step size). VARS is a novel global sensitivity analysis (SA) technique that uniquely characterizes perturbation scale dependency of SA. The sensitivity analysis strategies are preferred that take into account the impact of parameter perturbation scale.